ß-catenin signaling is required for RAS-driven thyroid cancer through PI3K activation - Sastre-Perona, Ana (Oncotarget, 2016)
Mutations in ß-catenin are traditionally described as late events in thyroid cancer progression. However, the functional implications of ß-catenin dysregulation in the context of tumor initiating events remain unclear. The aim of this work was to investigate whether the two main oncogenic drivers in thyroid cancer, RAS and BRAF, could activate the Wnt/ß-catenin pathway. Expression of HRAS(V12) but not BRAF(V600E) in thyroid cells induced ß-catenin nuclear localization, increased ß-catenin-dependent transcriptional activity and inhibited GSK3ß. In a panel of human thyroid cancer cell lines representative of the main genetic events in thyroid cancer, ß-catenin activation was highly dependent on PI3K/AKT activity through its phosphorylation at S552, but not on MAPK. Silencing of ß-catenin expression in cell lines led to a dramatic reduction in proliferation due to an induction of senescence, which was concordant with a reduction in tumor size in nude mice. Moreover, ß-catenin silencing suppressed the expression of EMT-related genes and reduced the invasive capacity of the tumor cells. In conclusion, this work demonstrates that RAS-driven tumors induce PI3K/AKT-dependent ß-catenin activation.